Parthian Cataphract vs. the Roman Army 53 BC-AD 224 - SYVÄNNE, Ilkka (Historia i Świat, 2017)
This article provides a short overview of the Parthian military and it tactics, and what were the Roman responses to that and what were the Parthian countermeasures against the Roman methods from ca. 53 BC until AD 224. It also suggests that when the sources claim that the Parthian monarchs fielded massive numbers of cataphract cavalry that we should really accept what these sources state: namely that the entire Parthian cavalry force of Parthia proper was really encased in armour as cataphracts.